CLOUD-BASED eDISCOVERY IN HEALTHCARE: OPTIMIZING COMPLIANCE AND LITIGATION PREPAREDNESS IN THE DIGITAL AGE - Padmapriya Nagineni (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Cloud-based eDiscovery solutions revolutionize how healthcare organizations manage electronic medical records (EMRs) and navigate complex regulatory landscapes. This article examines the implementation and impact of cloud eDiscovery platforms in healthcare settings, focusing on their role in enhancing HIPAA compliance and litigation readiness. Through a comprehensive analysis of current literature, case studies, and expert interviews, we explore how these technologies streamline data processing, ensure secure storage, and facilitate real-time collaboration among medical professionals, legal teams, and compliance officers. Our findings indicate that cloud-based eDiscovery significantly reduces the risk of non-compliance fines, accelerates the legal discovery process, and improves overall organizational agility in responding to regulatory demands. However, challenges such as data security concerns and integration with existing healthcare IT systems persist. This research provides valuable insights for healthcare administrators, legal professionals, and policymakers on the transformative potential of cloud eDiscovery in addressing the growing complexities of healthcare data management and compliance.